ИДЕЙНЫЕ ПЕРВОИСТОЧНИКИ В СТРОИТЕЛЬСТВЕ НАЦИОНАЛЬНОГО ОБРАЗОВАНИЯ В АЗЕРБАЙДЖАНСКОЙ ДЕМОКРАТИЧЕСКОЙ РЕСПУБЛИКЕ. - Исмайлова, Нигяр (Journal of Educational Sciences, 2016)
Сандаған ғасырлар бойы Азербайжандағы білім араб, парсы тілдерінің негізінде құрылды. 1830 жылдан бастап орысша білім алған зиялы қауым өкілдері Азербайжан халқының өз ана тілінде білім алуын армандап, ос ымақсат жолында күресін бастады. Мақалада Азербайжан демократиялық Республикасындағы ұлттық білім берудегі алғашқы идеялық қайнарларға тоқталады.Throughout many centuries education in Azerbaijan was under construction on the basis of the Arabian, Persian languages. Since 1830, the representatives of the intelligency who has got education in Russian, dreamt of training in Azerbaijan in a native language and have begunstruggle for realization of this dream. And already from second half of XIX-th century the idea about training in a native language, and already in the XX-th century beginning – creation of national textbooks more became more active.